Paleoseismological Findings at a New Trench Indicate the 1714 M8.1 Earthquake Ruptured the Main Frontal Thrust Over all the Bhutan Himalaya - Zhao, Yuqiu; Grujic, Djordje; Baruah, Santanu; Drukpa, Dawchu; Elkadi, Joanne; Hetényi, György; King, Georgina E.; Mildon, Zoë K.; Nepal, Nityam; Welte, Caroline (Frontiers in Earth Science, 2021)
The 1714 Bhutan earthquake was one of the largest in the Himalaya in the last millennium. Nevertheless, until few years ago, Bhutan Himalaya were regarded as a seismic gap with a large potential for slip. We show that the surface rupture caused by this earthquake was at least 175 km long, with slip exceeding 11 m at our study site. The age of the surface rupture was constrained by combination of radiocarbon and traditional optically stimulated luminescence dating of affected river sediments. Computations using empirical scaling relationships yielded plausible magnitude of Mw 8.1 ± 0.4, and placed the epicentre of the 1714 Bhutan earthquake on the flat segment of the Main Himalayan Thrust (MHT), the basal décollement of the Himalayan orogen. Calculations of Coulomb stress transfer indicate that large earthquakes along the proximal part of the MHT would cause surface rupture. In contrast, distal earthquakes would not immediately trigger surface rupture although they would increase the stresses in the proximal part facilitating future surface-rupturing earthquakes. Distal, blind earthquakes would also transfer stress into the foreland basin facilitating southward propagation of the MHT in form of a blind basal décollement. In conclusion, studies of surface rupturing events alone, likely underestimate the seismic slip along the Himalayan megathrust.